Left ventricular thrombosis in acute anterior myocardial infarction: Evaluation of hospital mortality, thromboembolism, and bleeding. Issue 10 (16th October 2018) - Ram, Pradhum; Shah, Mahek; Sirinvaravong, Natee; Lo, Kevin Bryan; Patil, Shantanu; Patel, Brijesh; Tripathi, Byomesh; Garg, Lohit; Figueredo, Vincent
Abstract : Background: Left ventricular thrombosis (LVT) is a well‐known complication of acute myocardial infarction, most commonly seen in anterior wall ST‐segment elevation myocardial infarction (STEMI). It is associated with systemic thromboembolism. Hypothesis: Our aim was to evaluate the impact of LVT on in‐hospital mortality, thromboembolism, and bleeding in patients with anterior STEMI. Methods: Data was collected from the Nationwide Inpatient Sample where patients with a primary diagnosis of "Anterior STEMI" [ICD9‐CM code 410.1] were included. Comparisons were made between patients with LVT [ICD9‐CM code 429.79] vs those without using propensity score matching (PSM). Results: From 2002 to 2014, there were 157 891 cases of anterior STEMI. Among these, 649 (0.4%) had LVT. Post‐PSM, there was no difference in in‐hospital mortality between the groups with LVT and without (7.3% vs 8.6%). Thromboembolic event rate was higher with LVT compared to those without LVT (7.3% vs 2.1%). There was no difference in bleeding events between patients with LVT and those without (2.9% vs 3.2%). The baseline average length of stay in the group with LVT was longer than the group without LVT (7.9 ± 6.7 days vs 5.1 ± 6.0 days). The average hospitalization‐related costs were also significantly higher among patients with LVT compared to those without (95 598 USD vs 66 641 USD per stay) at baseline. Conclusion: Among patients hospitalized with anterior STEMI, presence of LVT is associated with increased thromboembolic events, average length of hospital stay and average cost of hospitalization. However, it is not associated with increased in‐hospital mortality or bleeding events.